EFEKTIVITAS DOODLING UNTUK MENINGKATKAN KEMAMPUAN PRAMENULIS BAGI ANAK TUNAGRAHITA RINGAN DI SLBN 2 PADANG SARAI - Tesi Putri Juwita (Universitas Negeri Padang, 2013)
This research background by fine motor problems in children Tunagrahita X is characterized by a child's hand fingers were stiff, so it makes the child have difficulty in learning to write, and therefore researchers wanted to improve pre-writing skills in children Tunagrahita using Activity Doodling. In this occasion is to connect the dots patterned like: diagonal, curved, circles and zig-zag. Type of research is a single research subject (single-subject research), the ABA design. The subjects were mild mental retardation children. Data were collected using a permanent form of product registration tests after being given treatment. The data collected were baseline (A1), treatment (B) and baseline (A2). Furthermore, the data were analyzed using visual analysis of the graph that consists of the analysis of the condition and between conditions. Once the data is analyzed, the obtained results: long baseline condition (A1) is 7 times of observation, for 7 days, the intervention condition (B) is over 10 times during the 10 days of observation, and the baseline condition (A2) is 7 times during the meeting 7 days. Baseline data showed a tendency toward a child's ability to move his hands to connect the dots patterned with a defined pattern slightly up, the intervention condition a child's ability to connect the dots patterned to increase the child can do the 9 pattern correctly, in addition the baseline condition (A2 ) the child's ability to connect the dots patterned also rose and data showed stability from the first day until the seventh day is to do the 9 patterns such as horizontal, vertical, diagonal, curved, circles and zig -zag. It can be concluded that the use of activity pre-writing Doodling can improve skills for children fifth grade mental retardation SLBN 2 Padang Sarai. It is suggested that principals and teachers to make the results of this study as a reference for the development of learning as children develop fine motor training effort in writing.